Effect of Progressive Solid Solution Treatment on the Structure and Properties of 316H Stainless Steel - Jing Xue, Xin Guanghan, Geng Xin, Jiang Zhouhua (Teshugang)
Regarding the requirement of residual ferrite content not exceeding 1% and grain size controlled within 4-6 levels in 316H austenitic stainless steel. Based on Thermo calc thermodynamic calculations and research on the changes in microstructure and properties during solid solution treatment， a progressive solid solution treatment method is proposed. The thermodynamic calculation results show that the solid solution temperature range for the formation of a single austenite structure in 316H steel is 975.5 ℃-1 281 ℃.Solid solution experimental research shows that the experimental steel treated with single stage solid solution can meet the requirements for residual ferrite content at 1 050 ℃ and 1 100 ℃， but the distribution of grain size is uneven and the phenomenon of mixed crystals is severe， leading to an increase in plasticity and toughness of the experimental steel， but the strength is obviously decreased. Adopting a progressive solid solution treatment of 1 000 ℃ （1 h）+1 100 ℃ （1 h）， while ensuring that the ferrite content and grain size meet the requirements， the uniformity of the structure is significantly improved， and the strength and toughness of the sample are higher than those of single stage solid solution treatment.